Authenticating turbocharger performance utilizing ASME performance test code correction methods - Shultz, Jacque (Kansas State University, 2011)
Continued regulatory pressure necessitates the use of precisely designed turbochargers to create the design trapped equivalence ratio within large-bore stationary engines used in the natural gas transmission industry. The upgraded turbochargers scavenge the exhaust gases from the cylinder, and create the air manifold pressure and back pressure on the engine necessary to achieve a specific trapped mass. This combination serves to achieve the emissions reduction required by regulatory agencies. Many engine owner/operators request that an upgraded turbocharger be tested and verified prior to re-installation on engine. Verification of the mechanical integrity and airflow performance prior to engine installation is necessary to prevent field hardware iterations. Confirming the as-built turbocharger design specification prior to transporting to the field can decrease downtime and installation costs. There are however, technical challenges to overcome for comparing test-cell data to field conditions. This thesis discusses the required corrections and testing methodology to verify turbocharger onsite performance from data collected in a precisely designed testing apparatus. As the litmus test of the testing system, test performance data is corrected to site conditions per the design air specification. Prior to field installation, the turbocharger is fitted with instrumentation to collect field operating data to authenticate the turbocharger testing system and correction methods. The correction method utilized herein is the ASME Performance Test Code 10 (PTC10) for Compressors and Exhausters version 1997.
Keywords: Turbocharger; Testing Verification; Centrifugal Compressor; Mechanical Engineering (0548)